Application of The C4.5 Algorithm to Get Customer Satisfaction Levels (Case Study : Toko Craft Palu, Jl. Setia Budi) - Resnawati; Ningrum, Desy Riani Sukma; Najar, Abdul Mahatir; Puspita, Juni Wijayanti (Program Studi Matematika, Universitas Tadulako, 2024)
Customer satisfaction refers to the response expressed by customers as a result of their evaluation of the perceived difference between their initial expectations before purchase and the performance of the service after purchase. Several specific factors impact the purchasing process and the performance of the product service, such as uncertainty in store operating hours and limited availability of inventory. These related issues have an impact on customer satisfaction, especially at Craft Palu store. The aim of this research is to determine the level of customer satisfaction and accuracy level using the decision tree method, specifically the C4.5 Algorithm. In this study, the measured variables of customer satisfaction at Craft Palu store are Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Based on the results of this research, it is found that Reliability is the most influential variable with an index value is 80,6% of respondents satisfied with the 5th statement, and accuracy test results using the C4.5 Algorithm in python software show an improvement with a decent final accuracy is 90%. Therefore, the C4.5 Algortihm is suitable for measuring customer satisfaction.